Intestinal and vaginal microbiota in pregnancy - Adonina, I. (Journal of Education, Health and Sport, 2025)
Background: Pregnancy induces profound hormonal, metabolic, and immunological changes that affect both maternal and fetal health. Increasing evidence highlights the role of intestinal and vaginal microbiota in shaping these processes, with dysbiosis linked to complications such as gestational diabetes, preeclampsia, preterm birth, and fetal growth restriction Objective: To investigate the composition and clinical significance of intestinal and vaginal microbiota during pregnancy, Methods: A mixed retrospective and prospective study was conducted at Odesa National Medical University (2021–2024). The retrospective analysis included over 600 medical records of pregnant women. The prospective cohort enrolled 412 women: 168 with MS and 244 controls. All underwent standardized clinical, biochemical, hormonal, and microbiological assessment. Placental samples were examined in 94 cases. Microbiota was evaluated using culture-based and molecular methods, with quantitative and qualitative assessment of bifidobacteria, lactobacilli, Enterobacteriaceae, Gardnerella, Candida, and Klebsiella. A subgroup of MS women received symbiotic therapy. Statistical analysis included multivariate regression and predictive modeling Results: Women with MS showed reduced bifidobacteria and lactobacilli, increased Enterobacteriaceae, and decreased microbial diversity. Vaginal dysbiosis was characterized by reduced Lactobacillus dominance and higher prevalence of Gardnerella and Candida. Combined dysbiosis strongly correlated with adverse outcomes and placental pathology. Symbiotic therapy improved microbial balance and significantly reduced rates of gestational diabetes, preeclampsia, preterm birth, cesarean delivery, and perinatal losses Conclusion: Intestinal and vaginal dysbiosis is common in MS pregnancies and predicts adverse outcomes. Symbiotic therapy offers a safe and effective strategy for restoring microbial balance and improving maternal and perinatal health.